Multiple Equilibrium, Variability, and the Development Process - Carranza, Luis.; Galdon-Sanchez, Jose. (Washington, D.C. : International Monetary Fund, 1998)
Per capita output is more volatile in middle-income economies than in both low-income and high-income economies. We examine this pattern in a two-period overlapping generations model with two productive sectors (a developed sector and a subsistence sector) and a credit sector. In the early and mature stages of development, there is a unique equilibrium, because labor and credit markets are cleared by a unique set of prices. In the middle stages of development, however, the model shows that markets can be cleared by a multiple set of prices. This multiplicity of equilibria arises as productive externalities are reflected in credit markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet